2023
DOI: 10.3390/foods12071364
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Sugars, Organic Acids, Mineral Composition, and Chilling Injury Sensitivity on Six Pomegranate Cultivars Stored at 2 °C

Abstract: Pomegranate is a sensitive fruit to chilling injury (CI) during storage at temperatures below 7 °C. However, sensitivity of pomegranate to CI is dependent on cultivar and exposure times to low temperatures. In this work, the sensitivity to CI of six pomegranate cultivars (Punica granatum L.) ‘Wonderful’, ‘Kingdom’, ‘Bigful’, ‘Acco’, ‘Purple Queen’, and ‘Mollar de Elche’, was evaluated after 30 d at 2 °C plus 2 d at 20 °C. Among cultivars, there was a great variability in the sensitivity to the appearance of CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In particular, peach fruit with higher concentration of sugars are more resistant to CI than those with lower concentrations (Brizzolara et al 2018 ; Tanou et al 2017 ; Wang et al 2013 ; Wu et al 2016 ; Yu et al 2015 ; Yu et al 2017 ; Zhang et al 2020 ) and in turn CI causes a decrease of sugars in fruit (He et al 2018 ; Monti et al 2019 ). The link between sugar metabolism and CI has been also reported in fruits such as pear, banana, tomato, bell pepper, and pomegranate (Delgado‐Vargas et al 2022 ; Gómez et al 2009 ; Liu et al 2019a ; Lorente-Mento et al 2023 ; Xu et al 2023 ; Yang et al 2023 ). Several studies reported how the increased tolerance to CI observed in fruits in response to the application of exogenous treatments was connected to the enhancement of sugar metabolism (Zhang et al 2021 ).…”
Section: Metabolomics Of Peach Exposed To Chilling Temperaturesmentioning
confidence: 82%
“…In particular, peach fruit with higher concentration of sugars are more resistant to CI than those with lower concentrations (Brizzolara et al 2018 ; Tanou et al 2017 ; Wang et al 2013 ; Wu et al 2016 ; Yu et al 2015 ; Yu et al 2017 ; Zhang et al 2020 ) and in turn CI causes a decrease of sugars in fruit (He et al 2018 ; Monti et al 2019 ). The link between sugar metabolism and CI has been also reported in fruits such as pear, banana, tomato, bell pepper, and pomegranate (Delgado‐Vargas et al 2022 ; Gómez et al 2009 ; Liu et al 2019a ; Lorente-Mento et al 2023 ; Xu et al 2023 ; Yang et al 2023 ). Several studies reported how the increased tolerance to CI observed in fruits in response to the application of exogenous treatments was connected to the enhancement of sugar metabolism (Zhang et al 2021 ).…”
Section: Metabolomics Of Peach Exposed To Chilling Temperaturesmentioning
confidence: 82%